2021
DOI: 10.1016/j.jss.2020.10.028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preoperative Botulinum Toxin A Injection on Abdominal Wall Reconstruction

Abstract: Background: Fascial closure significantly reduces postoperative complications and hernia recurrence after abdominal wall reconstruction (AWR), but can be challenging in massive ventral hernias.Methods: A prospective single-institution cohort study was performed to examine the effects of preoperative injection of botulinum toxin A (BTA) in patients undergoing AWR for midline or flank hernias.Results: A total of 108 patients underwent BTA injection with average 243 units, mean 32.5 days before AWR, without compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
1
16
0
10
Order By: Relevance
“…Examining the outcomes of use of botulinum toxin (BTA) in abdominal wall reconstruction, Deerenberg et al (38) reported on a cohort of 108 patients with large incisional hernias with loss of domain that underwent preoperatively botulinum injection under Computer Tomography fluoroscopic or ultrasound guidance. No complications from the injection were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Examining the outcomes of use of botulinum toxin (BTA) in abdominal wall reconstruction, Deerenberg et al (38) reported on a cohort of 108 patients with large incisional hernias with loss of domain that underwent preoperatively botulinum injection under Computer Tomography fluoroscopic or ultrasound guidance. No complications from the injection were reported.…”
Section: Resultsmentioning
confidence: 99%
“…When Nielsen et al looked at the long-term safety of BTX, it was given on "clinical suspicion of difficult closure, " with additional CS if necessary (13). Similarly, when Deerenberg produced a prospective study of 108 patients from the Carolinas Medical Centre, the decision to use BTX was based on opinion and discussion among expert hernia surgeons (14). Others have identified further qualitative CT findings such as shortened or thickened lateral abdominal muscles (12).…”
Section: Indications and Use With Pppmentioning
confidence: 99%
“…Some discrepancy in dosage between groups may be due to different BTX preparations, such as Botox R or Dysport R . In their largest, most recent paper Bueno Lledó et al (19) describe using Dysport R (Ipsen, Boulogne-Billancourt, France) whereas both Yurtkap et al (18) and Deerenberg et al (14) describe using Botox (Botulinum toxin Allergan, Inc., Irvine, California). Jacombs et al (17) describe using an equivalent dose of either of the two formulations.…”
Section: Dosagementioning
confidence: 99%
See 2 more Smart Citations